The Relationship Between Healthcare Worker Performance and the Incidence of Missing Medical Record Documents at the Batu Brak Community Health Center (UPTD) - Valinda, Yuni; Aziza, Nurul; Djamil, Achmad (Jurnal Manajemen Informasi Kesehatan (Health Information Management), 2025)
A document is a written or printed document that can serve as evidence or information, such as a birth certificate, marriage certificate, or other document. Data recorded at the Batu Brak Community Health Center (UPTD) in West Lampung Regency, from January to April 2024, recorded 39 (0.19%) incidents of misfiling medical record documents out of a total of 2,016 medical record documents. The purpose of this study was to analyze the relationship between healthcare worker performance and the incidence of misfiling medical record documents. The results showed that the highest percentage of healthcare workers' performance was poor (36, 59%), while 21 (41.0%) performed well. 37 (60.7%) did not misfiled medical record documents. However, for those who did misfiled, there was a relationship between healthcare worker performance and the incidence of misfiling medical record documents (p value = 0.026). It is recommended that the community health center further improve and maintain the performance of health workers, especially in carrying out their duties as medical records officers, so that they can properly maintain and store medical record documents.